Tax evasion and Nigeria tax system: An overview - Gurama, Zakariya’u; Mansor, Muzainah; Pantamee, Abdurrahman Adamu (IISTE, 2015)
Taxation is acknowledged as a very essential instrument for National Development and growth in many societies and nations in the world over centuries.Being among the main guides by whom development and growth ought to be measured in any civilization is the extent of wealth, which is generated by economic undertaken in that society.The main objective of this paper is to review the taxation and tax evasion concept and furthermore provide a brief overview of Nigerian tax system.The paper in an attempt to achieve it goals provide conceptual and empirical evidence of evilness of tax evasion and what motives behind the phenomenon globally.Furthermore, the paper provide brief but precise knowledge of Nigerian tax system, tax policy and underpinning tax law of the country.Similarly, objectives and guiding principle, driving institution of Nigerian tax system, administration and policy and concept of U-TIN where also discuss.